Severe Acute Flaccid Myelitis Associated With Enterovirus in Children: Two Phenotypes for Two Evolution Profiles? - Aubart, Melodie; Gitiaux, Cyril; Roux, Charles Joris; Levy, Raphael; Schuffenecker, Isabelle; Mirand, Audrey; Bach, Nathalie; Moulin, Florence; Bergounioux, Jean; Leruez-Ville, Marianne; Rozenberg, Flore; Sterlin, Delphine; et al. (Frontiers in Neurology, 2020)
Acute flaccid myelitis (AFM) is an acute paralysis syndrome defined by a specific inflammation of the anterior horn cells of the spinal cord. From 2014, worrying waves of life-threatening AFM consecutive to enterovirus infection (EV-D68 and EV-A71) have been reported. We describe 10 children displaying an AFM with an EV infection, the treatments performed and the 1 to 3-years follow-up. Two groups of patients were distinguished: 6 children (« polio-like group ») had severe motor disability whereas 4 other children (« brainstem group ») displayed severe brainstem weakness requiring ventilation support. Electrodiagnostic studies (n=8) support the presence of a motor neuronopathy associated to myelitis. The best prognosis factor seems to be the motor recovery after the first 4 weeks of the disease.